Characterization of a new bifunctional endo-1,4-β-xylanase/esterase found in the rumen metagenome - Pavarina, Gabriella Cavazzini [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP]; Lima, Natália Sarmanho Monteiro [UNESP]; Pizauro Jr, João Martins [UNESP] (Springer Nature, 2021)
Metagenomic data mining of the Nellore cattle rumen microbiota identified a new bifunctional enzyme, endo-1,4-β-xylanase/esterase, which was subsequently overexpressed in E. coli BL21 (DE3). This enzyme was stable at pH intervals of 5 to 6.5 and temperatures between 30 and 45 °C, and under the test conditions, it had a Vmax of 30.959 ± 2.334 µmol/min/mg, Km of 3.6 ± 0.6 mM and kcat of 2.323 ± 175 s−1. Additionally, the results showed that the enzyme is tolerant to NaCl and organic solvents and therefore is suitable for industrial environments. Xylanases are widely applicable, and the synergistic activity of endo-1,4-β-xylanase/esterase in a single molecule will improve the degradation efficiency of heteroxylans via the creation of xylanase binding sites. Therefore, this new molecule has the potential for use in lignocellulosic biomass processing and as an animal feed food additive and could improve xylooligosaccharide production efficiency.